Leisure time physical activity reduces the association between TV-viewing and depressive symptoms: A large study among 59,401 Brazilian adults - Werneck, André O. [UNESP]; Stubbs, Brendon; Fernandes, Rômulo A. [UNESP]; Szwarcwald, Célia L.; Silva, Danilo R. (Elsevier, 2019)
Background: Both physical activity (PA) and TV-viewing are associated with depressive symptoms, but the combined association with depressive symptoms is unclear. Therefore, our aim was to analyze the joint association of PA and TV-viewing with depressive symptoms among a large cohort of adults. Methods: We used data from the Brazilian National Survey, conducted in 2013 with 59,401 adults [≥18 years (34,282 women)]. Information regarding exposures (TV-viewing and leisure PA), outcome (depressive symptoms) and covariates (chronological age, race, educational status, employment status, tobacco smoking, alcohol consumption) were self-reported. Body mass index was estimated through the assessment of body mass and stature. Logistic regression models were used. Results: Engaging in >5 hours of TV viewing was associated with elevated depressive symptoms [13.1% (CI95%: 11.6%–14.7%) vs. 7.4% (95%CI:7.0%–7.8%)]. However, this association was nullified when people met guidelines and engaged in >150 min of PA per week. Specifically, among men [Active: OR = 1.16 (95%CI: 0.58–2.32) vs. Inactive: OR = 3.63 (95%CI: 2.43–5.42)] and women [Active: OR=1.30 (95%CI: 0.80–2.11) vs. Inactive: OR = 1.84 (95%CI: 1.43–2.36)]. Conclusion: Whilst TV viewing is associated with increased depressive symptoms, meeting recommended physical activity levels reduces the association between TV-viewing and depressive symptoms.
Keywords: Affective disorder; Depression; Exercise; Sedentary behavior; Sedentary lifestyle; Television